Implementation Of Rivest Chiper 6 and Blowfish Algorithm for Mobile-Based Message Cryptography - Ari Amir Alkodri; Supardi Supardi; Risky Maulana; Liza Fahreni (JURNAL SISFOTEK GLOBAL, 2022)
The development of technology in recent years has been very rapid, there are still many people who use short message technology, but the security aspect is not guaranteed. People who exchange information are at risk of having information content theft during the delivery process, for that it is necessary to encrypt messages before sending and decrypt them to be read so that they are not easily misused by unauthorized people. With Rivest Cipher 6 and Blowfish cryptographic algorithms, this model is a symmetric key algorithm in the form of a block cipher that can answer message security. This method is suitable for maintaining message security. In this paper, a number of aspects of cryptography will be discussed as well as the basic concepts of cryptography. The purpose of the application is designed to be able to implement the Rivest Ciper 6 and Blowfish algorithms. Rivest Chiper 6 and Blowfish algorithms implemented on android smartphones can encrypt messages before they are sent and decrypt messages when they are received, by using two message security encryption options, users can distinguish the results of the two algorithms and become more secure. In the encryption and decryption process, a key is needed to scramble and restore the contents of the message. The key is obtained when the sender and recipient met previously can also send the key through the application, but the key sent will be immediately deleted by the application so that others do not know the key to open the message.